La puesta en valor de la ciclovia 25 de Junio (By Pass) para el desarrollo del turismo interno del cantón Babahoyo - Torres Filian, Zaida Elita (2020)
The Babahoyo canton, which belongs to the province of Los Ríos, has several tourist attractions that make national and foreign tourists appreciate the different places this beautiful canton has. With the purpose of increasing tourism in the BY PASS of the Babahoyo canton, it is essential to give the respective value to the route of the ciclovía, having as main objective to determine the impact caused by the ciclovía in the development of tourism in the Babahoyo canton. Through the theoretical framework it was possible to appreciate and understand the bibliographic research that contributed to the development of the research work, in the same way through the research techniques it was possible to detect several problems that occur in the ciclovía, the participation of the inhabitants and the pertinent governmental entities. On the other hand, the respective analysis of the surveys made to the inhabitants of the 25 de junio avenue is made, where relevant information was extracted about those aspects that should be taken into account to improve the route of the ciclovía. Through the results obtained in the investigation, it was possible to determine the possible solutions to the problems found, and to culminate the necessary conclusions are developed for the implementation of the improvements of the ciclovía in the Babahoyo canton and thus to promote with the internal tourism and to improve with it the economic development of a certain place.